Trends in eggshell thickness and mercury in common goldeneye and hooded merganser eggs - David P. Rave; Michael C. Zicus; John R. Fieberg; Lucas Savoy; Kevin Regan (Wildlife Society Bulletin)
ABSTRACT Environmental contaminants such as dichloro diphenyl trichloroethane (DDT), polychlorinated biphenyls (PCBs), and mercury are associated with physiological problems in wildlife. DDT and PCBs were banned in North America in the 1970s, but these contaminants sometimes persist in the environment and can cause reproductive problems, including eggshell thinning. In contrast, mercury deposition from anthropogenic sources is a continuing if not growing concern globally. We measured thickness of common goldeneye (Bucephala clangula) and hooded merganser (Lophodytes cucullatus) eggshells collected in 2003–2004 in Minnesota, USA, to compare with measurements taken prior to (approx. 1900) and after (1981) widespread DDT use. We also compared egg‐mercury concentration (ppm) in goldeneye and merganser eggs collected in 2003–2004 with a 1981 collection. Mean eggshell thickness was 0.401 mm (SE = 0.003) and 0.606 mm (SE = 0.008) for goldeneyes and mergansers, respectively. This was 9.0% (goldeneyes) and 6.0% (mergansers) greater than in 1981. Mean thickness of goldeneye eggshells remained 7.8% less than the mean prior to widespread DDT use; whereas, merganser eggshell thickness was statistically similar to pre‐DDT thickness. Mean Ratcliffe's index, a measure of eggshell quality, also increased for goldeneyes (2.52, SE = 0.021) and mergansers (3.78, SE = 0.042) since 1981. Goldeneye values were statistically similar to, while merganser values remained 5.6% less than, pre‐DDT values. Geometric mean concentrations of mercury (wet wt) have declined since 1981 in merganser eggs (0.33 ppm, SE = 0.024), and were statistically unchanged in goldeneye eggs (0.13 ppm, SE = 0.011). Continued monitoring of wildlife populations for contaminants is important because wildlife may serve as an indicator of overall ecosystem health. © 2013 The Wildlife Society.